From 'Year 9 dropout' to doctoral candidate: An autoethnographic journey of becoming (with friends). Issue 6 (2nd November 2019) - Miles, Jennifer Kay; Creely, Edwin; Pruyn, Marc
ABSTRACT: In this article, I am joined by two academic colleagues to explore my personal narratives and experiences as a doctoral student, and to explicate the challenges and achievements of my pathway into doctoral studies. Positioning itself within the growing field of doctoral research, the article focuses on an exploration of three vignettes which identify important points in my unfolding stories of formation in becoming a doctoral student as an older person. This autoethnographic study draws on Transformative Learning Theory and the critical discourse understandings of Gee to examine my stories of becoming from school-leaver at 15 to doctoral student over four decades later. The study has three implications. First, it is important to recognise and appreciate alternate pathways to doctoral education. Second, that there is a need to better understand the complex formation of doctoral students within an academic research community; especially in regard to those from diverse or challenging backgrounds. Finally, the significance of seeing doctoral education as identity work and work of the soul, built as much on affective experiences and reflexivity as learning to perform and write as an academic, is key.